Effects of Silibinin on Delaying Aging in Drosophila melanogaster - Kai Zhu; Hang Ni; Eqra Hafeez; Yaxuan Hu; Fan Hu; Dongsheng Du; Dongsheng Chen (Antioxidants, 2025)
Aging is an inevitable physiological process, but delaying aging has always been an enduring human pursuit. Silibinin (SIL), derived from the seeds of the milk thistle plant, exhibits a broad spectrum of pharmacological properties, including anti-tumor effects, liver protection, inhibition of apoptosis, and alleviation of inflammation. However, whether it has anti-aging effects remains unclear. The SIL dietary supplement to Drosophila melanogaster prolonged lifespan, improved climbing ability, ameliorated age-associated intestinal barrier disruption, enhanced the resistance to oxidative stress, and increased the enzyme activities of superoxide dismutase (SOD) and catalase (CAT). Furthermore, RNA-seq results showed that SIL addition significantly upregulated 74 genes and downregulated 50 genes compared with the control. KEGG (Kyoto Encyclopedia of genes and genomes) analysis demonstrated that these differentially expressed genes were primarily involved in the Toll signaling pathway and endoplasmic reticulum proteins processing, six among which, including IM2, IM3, Drsl3, CG7556, GCS1, and TRAM, were particularly involved in the regulation by SIL supplementation. The results indicate that SIL exhibits anti-aging effects by enhancing antioxidant capacity and regulating aging-related signaling pathways. Therefore, SIL shows a potential application in anti-aging dietary regimens.